A Non Trivial Pursuit: - systems development as cooperation - Bødker, Susanne; Greenbaum, Joan (DAIMI Report Series, 1988)
In this paper we present some of the results of an empirical investigation of systems development project work. These results are the outcome of our attempts to ''listen to'' a project group developing a large computer application for a bank. It has been our primary purpose to catch the informal sides of project work, and this paper will focus on two aspects: Project work as group work as a means of creating something in common, this something being a computer application which will be used in a use-setting outside the project group. A comparison of our findings with different understandings of systems development project work found in literature is included, as is a discussion of our methodology.